2011
DOI: 10.1124/jpet.111.180943
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ingestive Behaviors in the Rat by GSK1521498, a Novel μ-Opioid Receptor-Selective Inverse Agonist

Abstract: ABSTRACT-Opioid receptor (MOR) agonism induces palatable food consumption principally through modulation of the rewarding properties of food. N-{ [3,5-difluoro-3Ј-(1H-1,2,4-triazol-3-ylis a novel opioid receptor inverse agonist that, on the basis of in vitro affinity assays, is greater than 10-or 50-fold selective for human or rat MOR, respectively, compared with -opioid receptors (KOR) and ␦-opioid receptors (DOR). Likewise, preferential MOR occupancy versus KOR and DOR was observed by autoradiography in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…Treatment with GSK1521498 dose-dependently reduced alcohol-seeking behavior and voluntary alcohol consumption in rP and rHAD1 rats more effectively than naltrexone and with a longer duration of effect significantly, reflecting its longer half-life. This apparently greater effectiveness of GSK1521498 is also convergent with prior results and is possibly because of the higher selectivity for the MOR (14-20-fold greater over δ-and κ-opioid receptors compared with 4-10-fold selectivity reported for naltrexone) or the 100-fold selectivity for MOR over nociceptin/orphanin receptors (Ignar et al, 2011;Kelly et al, 2014). Moreover, its more complete antagonist profile, and its lesser inverse agonist activity under some assay conditions, compared with the incomplete antagonism and partial agonist activity of naltrexone, also possibly contribute to the different behavioral profile of GSK1521498 (Ignar et al, 2011;Kelly et al, 2014).…”
Section: Effects Of Manipulating the Opioid System On Alcohol Seekingsupporting
confidence: 76%
See 1 more Smart Citation
“…Treatment with GSK1521498 dose-dependently reduced alcohol-seeking behavior and voluntary alcohol consumption in rP and rHAD1 rats more effectively than naltrexone and with a longer duration of effect significantly, reflecting its longer half-life. This apparently greater effectiveness of GSK1521498 is also convergent with prior results and is possibly because of the higher selectivity for the MOR (14-20-fold greater over δ-and κ-opioid receptors compared with 4-10-fold selectivity reported for naltrexone) or the 100-fold selectivity for MOR over nociceptin/orphanin receptors (Ignar et al, 2011;Kelly et al, 2014). Moreover, its more complete antagonist profile, and its lesser inverse agonist activity under some assay conditions, compared with the incomplete antagonism and partial agonist activity of naltrexone, also possibly contribute to the different behavioral profile of GSK1521498 (Ignar et al, 2011;Kelly et al, 2014).…”
Section: Effects Of Manipulating the Opioid System On Alcohol Seekingsupporting
confidence: 76%
“…We further compared its effects with those of a clinically approved treatment for alcoholism, naltrexone, that has previously been shown to reduce ethanol drinking (Davidson and Amit, 1997;Froehlich et al, 1990;HendersonRedmond and Czachowski, 2014) and cue-induced reinstatement (Ciccocioppo et al, 2002) in animal models, as well as to decrease cue-induced craving in human alcohol abusers (Rohsenow et al, 2000). Both compounds target the μ-opioid receptors (MORs), but GSK1521498 is a more selective MOR antagonist than naltrexone, and unlike naltrexone, has no partial agonist activity Kelly et al, 2014) and instead has, in some in vitro assays, minor inverse agonist activity (Ignar et al, 2011;Kelly et al, 2014). The effects of both treatments on CS-controlled alcohol-seeking behavior, alcohol intake during the free-access period earned by rats through making seeking responses, as well as in a home environment two-bottle choice procedure, were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, our results could be interpreted as a preference for lower carbohydrates and not for higher fat. However, rats prefer increasing (not decreasing) carbohydrate content 14,15 reducing the validity of this interpretation.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to include the middle-fat foods (15 %, 17.5 %, and 20 %) to visualize any shifts in the preference curve. The shifts in the fat preference curve can be interpreted similarly to how the various two-bottle choice preference tests are interpreted 13,14 . As the rats have a bias toward eating high-fat food, a significantly decreased preference high-fat food represents a possible pharmacologically relevant change in food composition choices.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, naltrexone can act synergistically with bupropion as a fixed-dose combination to decrease body weight, possibly by increasing POMC neuronal activity [107]. GSK1521498 is a selective MOR antagonist/inverse agonist that was reported to induce a robust weight loss associated with a decrease in the intake of palatable foods in diet-induced obese animals [108]. In a 28-day study in binge-eating obese subjects, GSK1521498 was found to promote a significant reduction in the hedonic responses associated with sweetened dairy products and in the caloric intake of high-fat foods during buffet meals, but was not significantly different from placebo in its effects on body weight, fat mass and binge eating scores [109].…”
Section: Opioid Pathwaymentioning
confidence: 98%